Evolution Sustainable Innovation Management in China - A. P., Puvanasvaran (2012)
Innovation performance in China has become the focus of many studies. Rapid growth in China has brought the topic of innovation in China into discussion. In today business, innovation is the only way to achieve goals and objectives that lead to sustainable growth. Thus in this paper the question we proposed is how technical capabilities, R&D centers and research institutions, and human capital all together affect innovation performance in China. Previous studies on innovation in China have examined innovation performance regarding economic and marketing aspects. Following discussion highlights the importance of each variable base on number of studies has conducted to study that particular variable.